2009
DOI: 10.1111/j.1365-2567.2008.02958.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of type 1 diabetes in filaria‐infected non‐obese diabetic mice is associated with a T helper type 2 shift and induction of FoxP3+ regulatory T cells

Abstract: Summary We sought to determine whether Litomosoides sigmodontis, a filarial infection of rodents, protects against type 1 diabetes in non‐obese diabetic (NOD) mice. Six‐week‐old NOD mice were sham‐infected or infected with either L3 larvae, adult male worms, or adult female worms. Whereas 82% of uninfected NOD mice developed diabetes by 25 weeks of age, no L. sigmodontis‐infected mice developed disease. Although all mice had evidence of ongoing islet cell inflammation by histology, L. sigmodontis‐infected mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
104
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(111 citation statements)
references
References 33 publications
(60 reference statements)
7
104
0
Order By: Relevance
“…In addition, clinical trials in humans examining effects of helminth products on disease severity in autoimmune diseases have shown promising results, as well as showing the safety of these helminth-derived immunomodulators for use as therapeutic agents. Although there is evidence to show that helminth infection can prevent T1DM in mice, 11,13,[23][24][25] there are no reports to support this hypothesis in humans. Epidemiologic studies carried out in southern India have shown reduced prevalence of LF after mass drug administration.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In addition, clinical trials in humans examining effects of helminth products on disease severity in autoimmune diseases have shown promising results, as well as showing the safety of these helminth-derived immunomodulators for use as therapeutic agents. Although there is evidence to show that helminth infection can prevent T1DM in mice, 11,13,[23][24][25] there are no reports to support this hypothesis in humans. Epidemiologic studies carried out in southern India have shown reduced prevalence of LF after mass drug administration.…”
Section: Discussionmentioning
confidence: 88%
“…Our findings thus support the animal experiments that have shown that infection with the filarial parasite was enough to confer protection against T1DM. 23 It is unlikely that the decreased prevalence of LF among persons with diabetes was caused by LF-mediated mortality because LF is a chronic, nonlethal disease. More studies are clearly needed on the prevalence of diabetes (T1DM and T2DM) and other infectious diseases to have a better understanding of the interplay of infection/ inflammation and diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that SEA enhanced the expression of Foxp3 in naive NOD-specific T cells in a TGF-b-dependent manner (34). Similarly, infection with Litomosoides sigmodontis-protected mice from diabetes in a Treg-and TGF-bdependent manner (5,35). Furthermore, we have previously shown that infection with live F. hepatica attenuated EAE in a TGF-bdependent manner and this was associated with an expansion of Tregs (7).…”
Section: Discussionmentioning
confidence: 99%
“…Surgical implantation of L. sigmodontis adults into BALB/c mice reduced induced allergic airway inflammation and hyperreactivity in a model for OVA-induced asthma (30). Also, onset of type 1 diabetes was prevented by injection of L3 and implantation of adults (31), and LPS-induced sepsis was slightly mitigated by adult implantation (22). Finally, it was shown that a preexisting natural L. sigmodontis infection prevented the development of cerebral malaria in C57BL/6 mice coinfected with Plasmodium berghei ANKA (32).…”
mentioning
confidence: 92%